2007
DOI: 10.1038/sj.onc.1210208
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis of early and advanced gastric cancers

Abstract: Gastric carcinoma is one of the major causes of cancer mortality worldwide. Early detection results in excellent prognosis for patients with early cancer (EGC), whereas the prognosis of advanced cancer (AGC) patients remains poor. It is not clear whether EGC and AGC are molecularly distinct, and whether they represent progressive stages of the same tumor or different entities ab initio. Gene expression profiles of EGC and AGC were determined by Affymetrix technology and quantitative polymerase chain reaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 34 publications
(35 reference statements)
6
68
0
2
Order By: Relevance
“…Moreover, 20 novel gastric cancer-related genes were identified ( Table 2). The previous gene expression microarray studies of gastric cancer have reported several genes that show deregulated gene expression in gastric cancer (Hasegawa et al, 2002;Hippo et al, 2002;Boussioutas et al, 2003;Chen et al, 2003;Tay et al, 2003;Jinawath et al, 2004;Kim et al, 2007;Vecchi et al, 2007;Yang et al, 2007b;Myllykangas et al, 2008;Takeno et al, 2008;Tsukamoto et al, 2008). Our study correlated well with these previous studies as 17 of the 37 genes (46%) identified in our study were deregulated also in at least one of the previous studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, 20 novel gastric cancer-related genes were identified ( Table 2). The previous gene expression microarray studies of gastric cancer have reported several genes that show deregulated gene expression in gastric cancer (Hasegawa et al, 2002;Hippo et al, 2002;Boussioutas et al, 2003;Chen et al, 2003;Tay et al, 2003;Jinawath et al, 2004;Kim et al, 2007;Vecchi et al, 2007;Yang et al, 2007b;Myllykangas et al, 2008;Takeno et al, 2008;Tsukamoto et al, 2008). Our study correlated well with these previous studies as 17 of the 37 genes (46%) identified in our study were deregulated also in at least one of the previous studies.…”
Section: Discussionmentioning
confidence: 97%
“…Specific gene expression profiles which correlate with histology (Hippo et al, 2002;Boussioutas et al, 2003;Chen et al, 2003;Kim et al, 2003;Jinawath et al, 2004), invasiveness (Hasegawa et al, 2002;Hippo et al, 2002) and survival (Chen et al, 2003;Tay et al, 2003;Vecchi et al, 2007) have been identified in gastric cancer including a number of genes with a potential role in gastric carcinogenesis. The number of common genes reported in these studies is rather low, which is most likely due to the different patient populations, processing of the samples, microarray platforms, and analysis principles.…”
Section: Introductionmentioning
confidence: 96%
“…We would like to speculate that cyclin D2 increases the cycling of cells in colonization site since the growth of metastases from HM is slightly higher than that of NM (see Table 1). Col5a3 messenger was found to be associated with metastatic potential of squamous cell carcinoma [20,21], and Col8a1 protein-with the progression of gastrointestinal stromal cancers [22,23], although its prognostic value has not yet been clearly established. Mmp14 has been linked to poor prognosis of breast cancer because of an association with the presence of lymph node metastases [24,25].…”
Section: Discussionmentioning
confidence: 97%
“…tumor progression including tumor depth, lymph node metastasis and peritoneal seeding [46][47][48] , histological type (e.g. intestinal or diffuse) [49][50][51] and acquired drug resistance [52,53] .…”
Section: Carcinogenesis Of Gastric Cancer (Epigenetic Regulation Micmentioning
confidence: 99%